Immunogenicity at delivery after Tdap vaccination in successive pregnancies - De Weerdt, Louise; Thiriard, Anaïs; Leuridan, Elke; Marchant, Arnaud; Maertens, Kirsten (Frontiers in Immunology, 2024)
Background: Tetanus, diphtheria, acellular pertussis (Tdap) vaccination is recommended to be administered in every pregnancy. Although the safety of this strategy has been confirmed, the immunogenicity of Tdap vaccination in two successive pregnancies has not yet been described. This study investigated Tdap-specific immunity levels and transplacental transfer in two successive pregnancies after repeated Tdap-vaccination. Methods: Women enrolled in prior studies on Tdap vaccination during pregnancy were invited to participate in a follow-up study if they became pregnant again. Women who received a Tdap vaccine in both pregnancies were considered for this analysis. Tdap-specific total IgG and IgG subclasses were measured with a multiplex immunoassay. Results: In total, 27 participants with a mean interval between deliveries of 2.4 years were included in the analysis. In maternal serum, Tdap-specific total IgG levels were comparable at both deliveries whereas in cord serum, all Tdap-specific total IgG antibody levels were reduced at the second compared to the first delivery. This was largely reflected in the IgG1 levels in maternal and cord serum. Transplacental transfer ratios of total IgG and IgG1 were also mostly reduced in the second compared to the first pregnancy. Conclusion: This study reports for the first time Tdap-specific total IgG and IgG subclass levels and transfer ratios after repeated Tdap vaccination in successive pregnancies. We found reduced transfer of most Tdap-specific IgG and IgG1 antibodies in the successive pregnancy. As pertussis-specific antibodies wane quickly, Tdap vaccination in each pregnancy remains beneficial. However, more research is needed to understand the impact of closely spaced booster doses during pregnancy on early infant protection against pertussis.